2012
DOI: 10.1007/s13197-012-0887-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant properties of mangosteen peel extract

Abstract: The growing interest in the replacement of synthetic food antioxidants by natural ones has fostered research on the screening of plant-derived raw materials for identifying new antioxidants. The special attention of research today is focused on inexpensive or residual sources from agricultural industries. Fruit peels as sources of powerful natural antioxidants are often the waste parts of various fruits from consumption and food industry. Among the fruit peels, mangosteen peel is an important source of natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
108
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(122 citation statements)
references
References 80 publications
2
108
0
2
Order By: Relevance
“…DPPH radical scavenging activity measures the antioxidant capacity of donating hydrogen atom to eliminate the DPPH radical (Suttirak and Manurakchinakorn 2014). The sample of the polysaccharide was dissolved in de-ionized water to get a series of solutions with different concentrations (0.125-4 mg/mL).…”
Section: Dpph Free Radical Scavenging Activitymentioning
confidence: 99%
“…DPPH radical scavenging activity measures the antioxidant capacity of donating hydrogen atom to eliminate the DPPH radical (Suttirak and Manurakchinakorn 2014). The sample of the polysaccharide was dissolved in de-ionized water to get a series of solutions with different concentrations (0.125-4 mg/mL).…”
Section: Dpph Free Radical Scavenging Activitymentioning
confidence: 99%
“…7 Mangosteen has been used as a traditional medicine in Southeast Asia and possesses biologically active compounds, including phenolic acids, xanthones, tannins, and anthocyannins. 7 Currently, mangosteen is popular as a botanical dietary supplement. Mangosteen has antioxidant, antibacterial, antifungal, anti-inflammatory, and anti-HIV activities in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…8 Mangosteen also exhibits central nervous system depressant, anti-inflammatory, and antiulcer activities in vivo. 8 Suttirak and Manurakchinakorn 7 reported that antioxidant activity of mangosteen pericarp extract is affected by several factors as follows: 1) during the maturation stage, young fruit pericarp has higher concentrations of total phenolics and total tannins, while mature fruit pericarp contains higher total flavonoid content; 2) in the extraction solvent, the antioxidant activity is dependent on the solvents that are used for extraction due to the different solvent polarities that result with different contents of compounds in the extracted material; and 3) in the material preparation, generally, mangosteen pericarp is subjected to a drying step, and the xanthone content and free radical scavenging activity are affected by drying methods, which cause either enzymatic or thermal degradation of xanthones.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations